2013
DOI: 10.1371/journal.pone.0072142
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Viral Load Are Synergistically Associated with CIN1

Abstract: PurposeWe investigated the association between alcohol consumption and risk of cervical intraepithelial neoplasia (CIN) and cervical cancer, and determined whether these associations were modified by human papillomavirus (HPV) viral load in high-risk HPV-positive women participating in the Korean HPV cohort study (KHPV).MethodsAmong the women recruited in the KHPV (n = 1,243) from March 2006 to December 2009, we analyzed normal cytology (n = 581) as control group, CIN1 (n = 299), CIN2/3 (n = 161), or cervical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 46 publications
3
30
2
1
Order By: Relevance
“…Although alcohol consumption may also be associated with the risk of developing low-grade lesions in HR-HPVpositive women (Min et al, 2013), we did not find similar results. However, we did not analyse the quantity of alcohol consumption per day, only whether the patient did or did not consume alcohol.…”
Section: Discussioncontrasting
confidence: 83%
“…Although alcohol consumption may also be associated with the risk of developing low-grade lesions in HR-HPVpositive women (Min et al, 2013), we did not find similar results. However, we did not analyse the quantity of alcohol consumption per day, only whether the patient did or did not consume alcohol.…”
Section: Discussioncontrasting
confidence: 83%
“…Furthermore, to our knowledge, the combined effect of HPV load and alcohol consumption on the risk of persistent HPV infection has not been studied. In our previous study on other hospital subjects, women positive for HR-HPV with a high viral load who also consumed alcohol had markedly increased risks of CIN 1 (OR 19.1), but not CIN 2/3 [20]. The observations of the present study together with previous findings suggest that the synergistic effect of alcohol and HR-HPV load on the risk of virus-related cervical diseases might be exerted during the relatively early stages of cervical cancer pathogenesis.…”
Section: Discussionmentioning
confidence: 81%
“…To investigate the combined effects of viral load and cigarette smoking, two studies reported an association between cigarette smoking and HPV-16 DNA load in cervical carcinoma in situ (CIS) development and low-grade cytological abnormalities [18], [19]. However, to our knowledge, except for our previous study [20], research on the combined effect of HPV load and alcohol consumption on cervical cancer development has not been undertaken.…”
Section: Introductionmentioning
confidence: 96%
“…There is, however, sparse literature on the association of alcohol consumption and the risk of developing cervical cancer[12]. Alcoholism was associated with an increased risk of the development of cervical intraepthielial neoplasia 1 in a study from Korea, p = 0.0001 [13]. In this study, the authors showed that alcohol consumption and high HPV DNA viral load were associated with the risk of CIN1, but not CIN 2/3 or cervical cancer in HPV-positive women[13].…”
Section: Discussionmentioning
confidence: 99%